FORMATION OF SCIENTIFIC OUTLOOK OF FUTURE SPECIALISTS - KEY TO EFFICIENCY OF EDUCATIONAL ACTIVITIES - T. Petrushanko; I. Lytovchenko; T. Bubliy; O. Kostyrenko (Ukrainian Medical Stomatological Academy, 2017)
Professional and educational atmosphere in medical schools should promote the proper formation of the personality of the future doctor in his development of critical analytical thinking, and as a result is the sustainable scientific outlook.